Thermal equilibrium as a predictor of growth efficiency in preterm infants - Heiter, Julia; Konow, Juliane; Koch, Jochim; Singer, Dominique; Ebenebe, Chinedu Ulrich (Frontiers in Pediatrics, 2024)
Introduction Providing adequate nutrition to preterm infants to achieve postnatal growth similar to intrauterine growth remains challenging due to the unpredictability of individual determinants. Material and methods We used a calculation program for infant incubators to compare the estimated heat balance with the caloric intake and growth rate in Very Low Birth Weight Infants (VLBWI). Results and discussion A group of 32 VLBWI was studied over a period of 14–28 days. An interrelationship between thermal equilibrium and growth rate was observed, with standardized incubator settings being unable to avoid periods of negative thermal balance and concomitantly poor growth rate. Conclusion Determining personalized incubator settings by means of a calculation program could help improve nutrition and growth in preterm infants.